2021
DOI: 10.1016/j.tsf.2021.138783
|View full text |Cite
|
Sign up to set email alerts
|

Spray coating vs. immersion for self-assembly of gemini perfluorinated phosphonic acids on indium tin oxide

Abstract: Self-assembled monolayers (SAMs) are widely used to engineer the surface properties of metals and metal oxide layers. This article reports the fabrication of gemini perfluorinated phosphonic acids SAMs on indium tin oxide (ITO). The self-assembled monolayers are to be used for patterning nickel lines by electroplating on ITO in order to obtain low-cost conductor grids on heterojunction solar cells. The aim is to develop large-scale, low-cost processes that will both reduce production times and produce strong, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…We therefore also explored rinsing films before they are annealed in order to remove a greater degree of material from the (still wet) film; an approach recently established to remove aggregates and multilayers of spray‐coated gemini perfluorinated phosphonic acid SAMs deposited on top of ITO. [ 65 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore also explored rinsing films before they are annealed in order to remove a greater degree of material from the (still wet) film; an approach recently established to remove aggregates and multilayers of spray‐coated gemini perfluorinated phosphonic acid SAMs deposited on top of ITO. [ 65 ]…”
Section: Resultsmentioning
confidence: 99%
“…We therefore also explored rinsing films before they are annealed in order to remove a greater degree of material from the (still wet) film; an approach recently established to remove aggregates and multilayers of spray-coated gemini perfluorinated phosphonic acid SAMs deposited on top of ITO. [65] In our experiments, we therefore explored the use of various numbers of "prerinse" steps, with this study guided by device optimization (Figure S3b, Supporting Information) with the optimized rinse/prerinse protocol developed in Figure 1c. It was found that a single prerinse, in combination with a postrinse, was beneficial when applied to films that had been spray-cast, but instead was detrimental when applied to devices made from films deposited using an airbrush or spin coating.…”
Section: Developing Spray-coated Self-assembled Monolayersmentioning
confidence: 99%
“…Thereafter, a 5 mM solution of ODPA in isopropanol was used for the surface treatment of the ITO. 20 The surface treatment was made by dip-coating of ITO/glass in the ODPA solution for ∼5 h under the ambient condition (further details are provided in the Supporting Information). Following this, the surface functionalization, UV−ozone exposure (Novascan Technologies Inc., PSD-UVT Series, USA) was applied over a shadow mask.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the ITO/glass film was first cleaned using solvents and UV–ozone treatment, as noted above. Thereafter, a 5 mM solution of ODPA in isopropanol was used for the surface treatment of the ITO . The surface treatment was made by dip-coating of ITO/glass in the ODPA solution for ∼5 h under the ambient condition (further details are provided in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…While chain chemistry of PA plays an important role in masking properties of SAMs, the deposition method also has a significant effect. , Numerous deposition procedures of PA SAMs on ITO are found in the literature ,,,, and a lack of consensus remains. Deposition via immersion is the predominant method, with times ranging from minutes to days .…”
Section: Introductionmentioning
confidence: 99%